Digital Integration of Traditional Craft Motifs in Mobile AR/VR Interactive Art Creation - Chen, Zhijuan; Li, Xijin (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid advancement of digital technology and mobile augmented reality (AR) or virtual reality (VR), the digital integration of traditional craft motifs into contemporary art has emerged as a significant research focus. Traditional craft motifs embody profound cultural heritage and artistic value, and their distinctive visual characteristics offer substantial potential for digital artistic expression. The immersive and interactive affordances of mobile AR/VR technologies provide a novel paradigm for artistic creation. The effective integration of traditional craft motifs into mobile AR/VR interactive art is a critical pathway for both cultural heritage preservation and the advancement of contemporary artistic expression. However, existing style transfer algorithms and techniques remain constrained by limitations in content feature preservation, stylistic fidelity, and expressive capacity in interactive art contexts. To address these challenges, a novel diffusion model-based style transfer algorithm tailored for mobile AR/VR interactive art was proposed, enabling the effective extraction and transfer of visual features from traditional craft motifs. This approach emphasizes the preservation of cultural and artistic integrity throughout the style transfer process. Furthermore, an inversion-based feature condition acquisition method was introduced, alongside a two-stage inversion strategy designed to retain essential content features, thereby overcoming prevalent issues such as content loss and insufficient style transfer effect. These innovations not only significantly enhance both the visual quality and expressive power of traditional motifs within mobile AR/VR environments but also contribute to the convergence of digital art and cultural preservation, offering new pathways for inspiration and technique in contemporary interactive art creation.